Creating Synergy: Essential Components of a Successful R25E Cancer Education Program - Gronemeyer, Suzanne A. (Journal of cancer education, 2011)
For an R25E cancer research program to be a resounding success for both participating students and faculty, and to maintain federal funding, many synergistic elements are necessary. Essential components of the R25E Pediatric Oncology Education Program at St. Jude Children's Research Hospital include (1) a unique focus, (2) a program director who is passionate about the program and who is enthusiastically supported by the institution, (3) committed and involved faculty mentors, (4) a current and complete program website with an online application process, (5) a large external network referring top students to the program, (6) an extensive, diverse, and highly qualified applicant pool with rigorous application requirements, (7) meticulous matching of faculty mentors with mentees, (8) adequate financial support for participants (stipend and housing), (9) an outstanding basic science and clinical research infrastructure, (10) training in the protection of human subjects, the responsible conduct of research, and research with vertebrate animals, (11) a comprehensive lunch and learn seminar series, (12) oral and written participant presentations of their research results, (13) ongoing internal and external program evaluation, (14) long-term tracking of participants, and (15) continuing program innovation.